Fuerzas sistémicas en la construcción del orden regional sudamericano: El rol de la hegemonía estadounidense - Ayala Castiblanco, Lizeth Vanessa (2017)
The creation of the Union of South American Nations (Unasur) in 2008 seemed to encourage the formation of an alternative regional order to the inter-American system led by the United States. This project emerged in a context characterized by the failure of the FTAA, Brazil's international projection and the strength of South American countries to face the global economic crisis. Such conditions led to the diffusion of post-hegemonic readings to understand the regionalization of South America. Nowadays, however, the quest for regional autonomy is limited both by domestic and regional factors and by systemic forces involved in shaping new regional orders.As part of its nearest influence zone, United States has vital interests in South America that may collide with projects of regional autonomy. Given this context, it is necessary to review how the US hegemony has evolved in the region and how it interrelates with the construction of a South American order. For this purpose, this research will analyze the changes occurred during the presence of the United States in the region at economic, military, political and ideological level. Using a historical perspective, the study finds partial hegemonic declining tendencies that allow a greater agency capacity for the formation of a South American order. However, recent data shows that US economic and military primacy continues to be projected through its major regional partners, questioning the hypothesis of a significant decline in its hegemony.